Magnetic resonance imaging of white matter in Alzheimer's disease: a global bibliometric analysis from 1990 to 2022 - Yue, Jin-huan; Zhang, Qin-hong; Yang, Xu; Wang, Peng; Sun, Xu-Chen; Yan, Shi-Yan; Li, Ang; Zhao, Wei-Wei; Cao, Dan-Na; Wang, Yang; Wei, Ze-Yi; Li, Xiao-Ling; et al. (Frontiers in Neuroscience, 2023)
Background: Alzheimer’s disease (AD) is a common, progressive, irreversible, and fatal neurodegenerative disorder with a rapidly increasing worldwide incidence. Although much research on magnetic resonance imaging (MRI) of the white matter (WM) in AD has been published, no biliometric analysis study has investigated this issue. Thus, this study aimed to provide an overview of the current status, hotspots, and trends in MRI of WM in AD. Methods: We searched for records related to MRI studies of WM in AD from 1990 to 2022 in the Web of Science Core Collection (WOSCC) database. CiteSpace (version 5.1.R8) and VOSviewer (version 1.6.19) software were used for bibliometric analyses. Results: A total of 2199 articles were obtained in this study. From 1990 to 2022, the number of published papers showed an exponential growth of y = 4.1374e0.1294x, with an average of 17.9 articles per year. The top country and institution were The United States and University of California Davis, accounting for 44.52% and 5.32% of the total studies, respectively. The most productive journal was Neurology and the most co-cited journal was Lancet Neurology. Decarli C was the most productive author. The current research frontier trend focuses on the association between small vessel disease and AD, clinical application and exploration of diffusion MRI, and related markers. Conclusion: This study provides an in-depth overview of publications on MRI of WM in AD, identifying the current research status, hotspots, and frontier trends in the field.